2016
DOI: 10.1007/s00367-016-0435-9
|View full text |Cite
|
Sign up to set email alerts
|

Drones as tools for monitoring beach topography changes in the Ligurian Sea (NW Mediterranean)

Abstract: Drones as tools for coastal monitoring: multi-temporal analysis of beach 2 topography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(117 citation statements)
references
References 51 publications
1
111
2
3
Order By: Relevance
“…Limited by the meteorological conditions (wind speed inferior to 70-80 km/h and no rain) and the study area size (typically of the order of 1km²), UAV and photogrammetric process present advantage to generate 3D point cloud and Digital Surface Model (DSM) with accuracy closed to LiDAR DSM (Haala, 2009). Several studies have demonstrated the performance of this survey process on coastal areas (Casella et al, 2016;Gonçalves and Henriques, 2015;Casella et al, 2014;Mancini et al, 2013) with a vertical accuracy of the DEM around +/-10 cm.…”
Section: Introductionmentioning
confidence: 96%
“…Limited by the meteorological conditions (wind speed inferior to 70-80 km/h and no rain) and the study area size (typically of the order of 1km²), UAV and photogrammetric process present advantage to generate 3D point cloud and Digital Surface Model (DSM) with accuracy closed to LiDAR DSM (Haala, 2009). Several studies have demonstrated the performance of this survey process on coastal areas (Casella et al, 2016;Gonçalves and Henriques, 2015;Casella et al, 2014;Mancini et al, 2013) with a vertical accuracy of the DEM around +/-10 cm.…”
Section: Introductionmentioning
confidence: 96%
“…La metodología de reconocimiento (Hudson, 1997) que consiste en la colocación de varillas de 3/8 de pulgadas con una longitud no mayor a 40 centímetros, utilizada durante la presente investigación dio resultados satisfactorios requiriendo bajos recursos para llevarla a cabo, sin embargo, es necesario tener puntos de referencia en sectores cercanos para hacer el replanteo de nuevos sitios si los puntos colocados se pierden por la erosión o por intervenciones antrópicas o de animales. El uso de drones o UAV (Vehículos Aéreos no Tripulados) facilitaría la obtención de resultados ya que pueden usarse para obtener modelos de elevación y comparar los cambios en el tiempo (Casella et al, 2016).…”
Section: Discusión Y Conclusiones De Resultadosunclassified
“…SfM workflows are well-established [19,30,31] and are minimally elaborated here. Detailed processing steps, including optimization parameters, are presented in Table A1 and distributed in the published data [20].…”
Section: Structure-from-motionmentioning
confidence: 99%
“…Unmanned Aerial Systems (UAS; sometimes referred to as drones) coupled with Structure-fromMotion (SfM) photogrammetry offer a rapidly mobilized, and underutilized coastal surveying alternative that can provide high-resolution aerial coverage to quickly assess storm impacts and monitor recovery [17,19]. In this study, we evaluate the ability of these systems to map and measure coastal features in areas with sandy shores and semi-vegetated dunes.…”
Section: Introductionmentioning
confidence: 99%